Implementasi Algoritma Haversine Pada Absensi Kepegawaian Berbasis Android - Hidayatul Sidiq; Deni Satria; Humaira (Journal of Applied Computer Science and Technology, 2022)
At this time the development of the era is much influenced by technology. This development has an impact on various aspects and fields in the expected life in the field of employment. Al-Azhar 32 Padang Islamic Elementary School is one of the private schools located in the city of Padang, West Sumatra. Al-Azhar schools have staff such as principals, teachers and administration so that the data entered is quite a lot.The staffing system at the Al-Azhar school is still manual by inputting it with excel. To take attendance at the employee using fingerprints and some use the attendance form. However, errors often occur during scanning because the scanner cannot detect someone's finger when the scanner is dirty. So that many employees update attendance by filling out the attendance update form. Given the problems above, it is possible to propose a mobile-based personnel application system. This staffing application has various features that can be used for taking attendance, leave forms, attendance history, school information, and employee profiles. This Android-based attendance can only be taken around the school or less than 20 meters from the school distance. To find out the distance between th0e user and the school, this attendance application uses the haversine algorithm to measure the distance between the user and the school